Teat necrosis in newborn gilts - Schoneweis, D.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Marked enlargement and edema of the vulva are often noted in newborn gilts. An accompanying, but less conspicuous, lesion is enlarged, engorged mammary glands. Although not fully understood, the changes are thought to result from increased estrogen in sows before they farrow. The edema of the vulva usually causes no lasting problems but enlarged mammary glands are more susceptible to injury from a rough surface like concrete slats. Such injuries may lead to teat necrosis and fibrosis, which makes nipples appear inverted and they are often nonfunctional when the gilts farrow. The incidence of teat necrosis can be reduced by carpeting or other materials that protect pigs underlines from rough surfaces. Applying a protectant like Knee-Kote® to the underline of the gilts shortly after they are born and again whenever they are handled the first few days of life may further reduce the incidence.
Keywords: Swine; Teat necrosis; Newborn gilts; Farrow